Key Issues and Challenges for Managing and Evaluating B2B E-Commerce Projects within the Australian Pharmaceutical Supply Chain - Lin, Chad; Jalleh, Geoffrey (Medical Science Reference, IGI Global, 2012)
The use of Business-to-Business (B2B) e-commerce within the Australian pharmaceutical supply chain can potentially assist in setting up an infrastructure which supports complex, multiparty Internet-based trading and transactions among pharmaceutical manufacturers, wholesalers, hospitals, pharmacies, medical supply importers and exporters, and other players in the healthcare system. Effective use of B2B e-commerce can help these organizations reduce costs in supplying and distributing medicines and other medical-related products to the general public. However, despite high expectations for realizing the benefits of B2B e-commerce in the pharmaceutical supply chain, issues surrounding its evaluation and management remain poorly understood and relatively under-researched. This chapter presents case study findings on key management and evaluation issues and challenges in adopting and utilizing B2B e-commerce systems on eight pharmaceutical organizations in Australia. The key objectives of this study are: (1) to establish current practices and norms in evaluating B2B e-commerce investments and projects in the pharmaceutical industry; and (2) to identify key B2B e-commerce management issues and challenges within the Australian pharmaceutical supply chain. A key contribution of this chapter is the identification and examination of key issues and challenges faced by the pharmaceutical organizations undertaking B2B e-commerce activities within their supply chain. The findings will guide senior executives in these organizations to develop their own approaches or strategies to manage the opportunities and threats that exist in the Australian pharmaceutical supply chain.